Silver clusters deposited into polymers, aerogels and ionic liquids studied with X-ray and optical spectroscopy - Engemann, David Christopher (Technische Universität Dortmund, 2014)
Nanoparticles are quoted as a future technology. Especially silver (Ag) nanoparticles exhibit a great potential due to their optical activity and their anti-microbial behaviour. The deposition of clusters (consisting of about 250 Ag atoms) enables the functionalization of the clusters before they are deposited into or onto a substrate. The properties and the potential areas of application for those clusters vary with the kind of the substrate. In the present thesis Ag clusters were deposited into three different substrates by a supersonic nozzle expansion source. These are silica aerogel (SiO2 aerogel), polydimethylsiloxane (PDMS) and the room temperature ionic liquid 1-butyl-3-methylimidazolium hexa uorophosphate (BMIM PF6). Especially the properties of the clusters in the room temperature ionic liquid are of great interest due to the emerging scientific interest in those green solvents. The optical, structural, chemical and electronic properties were investigated using X-ray (X-ray absorption near edge structure, XANES) and optical (UV-Vis) spectroscopy. By plasmon resonance spectroscopy it was found that clusters in PDMS can be used as sensors to detect the presence of toxic H2S. Furthermore their shape in PDMS can be considered as spherical. The deposition of clusters into silica aerogel enables the investigation of high amounts of separated clusters. This is necessary for XANES experiments. These experiments yielded information on the density of unoccupied states of the clusters and showed differences in the 4d band struc- ture between cluster and bulk material. Additionally the electronic structures of clusters partially transformed to Ag2O and Ag2S were investigated. The deposition of clusters into BMIM PF6 enabled the investigation of the funda- mental properties of Ag clusters in the ionic liquid without the presence of any chemical additives as used in wet chemistry productions. It was found that the stability of the clusters in the ionic liquid is strongly in uenced by the purity of the ionic liquid and its temperature. Moreover the clusters can be fragmented by X-ray radiation which results in a XANES spectrum of micro clusters.
Keywords: Clusters; Nanoparticles; Silver; UV-VIS; XANES; Spectroscopy; PDMS; Aerogel; Ionic liquid; X-ray absorption; Plasmon resonance; Optical extinction; Cluster deposition; 530; Nanopartikel; UV-VIS-Spektroskopie; Röntgenspektroskopie; Oberflächenplasmonresonanz; Ionische Flüssigkeit